Clinical and morphological characteristics of ruptured small (<5 mm) posterior communicating artery aneurysms - Shibata, Aoto; Kamide, Tomoya; Ikeda, Shunsuke; Yoshikawa, Shinichiro; Tsukagoshi, Eisuke; Yonezawa, Azusa; Takeda, Ririko; Kikkawa, Yuichiro; Kohyama, Shinya; Kurita, Hiroki (Asian Journal of Neurosurgery, 2021)
Context: Small intracranial aneurysms (IAs) are considered to have a low risk of rupture; however, in clinical practice, we often encounter patients with subarachnoid hemorrhage (SAH) due to rupture of small IAs. Aims: This study aims to clarify the clinical and morphological characteristics of ruptured small IA, focusing on posterior communicating artery (PCoA) aneurysms as a prone site. Settings and Design: We retrospectively reviewed 102 consecutive patients with SAH due to ruptured PCoA aneurysm who underwent microsurgical or endovascular aneurysm repair between April 2013 and March 2018. Subjects and Methods: All PCoA aneurysms were diagnosed using three-dimensional rotation angiography or three-dimensional computed tomography angiography. Information regarding the following clinical characteristics was collected: age, sex, past medical history, current smoking, antithrombotic therapy, multiplicity, hydrocephalus, intracerebral hemorrhage, intraventricular hemorrhage, and World Federation of Neurosurgical Societies (WFNS) Grade on admission. Statistical Analysis Used: We analyzed factors of ruptured small IA, focusing on PCoA aneurysms using univariate and multivariate regression analyses. Results: Univariate and multivariate analyses revealed that low aspect ratio (AR) (odds ratio [OR] = 0.33, P = 0.01) and nonfetal type of PCoA (OR = 0.31, P = 0.02) might be independent characteristics of ruptured small PCoA aneurysms. However, age, sex, past medical history, WFNS grade, and treatment outcome were not different between the small and nonsmall PCoA aneurysms. The aneurysm size was not associated to the selection of treatment, proportion of complications, and treatment outcome. Conclusions: In cases of ruptured PCoA aneurysms, low AR and nonfetal type of PCoA might be associated with rupture of small aneurysms.